PENERAPAN KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) MATERI BAHASA INDONESIA DI SMP ISLAM AL-SYUKRO UNIVERSAL - Nuryani Nuryani (Jurnal Penelitian Humaniora, 2012)
The curriculum implemented in Indonesian education has undergone several changes. This is because education changes from time to time to match with the changes in the context of the era. One of the changes highlighted in the curriculum is materials for Indonesian language. Curriculum 2013 is currently ratified to replace the previous one, school unit based curriculum. Why is it so? This study tries to investigate the implementation of teaching learning process of Indonesian language in junior high school of SMP Islam Al-Syukro Universal. This is a case study, using qualitative method. The result of study reveals that school-based unit curriculum has been implemented in SMP Islam Al Syukro Universal, particularly in the teaching of Indonesian language. This is materialized in the lesson plans and the teaching learning process, covering learning objectives, the material presented, the methods used, and evaluations models.